Problems of search and diagnosis of carbonatites on the territory of Ukraine - Zahnitko, Vasyl (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Reliably established carbonatites on the territory of Ukraine have characteristics inherent in this class of rocks, in particular, they are enriched with a fairly wide range of rare chemical elements, the most characteristic are rare earth elements and strontium, niobium, tantalum, zirconium. In addition, they contain typomorphic minerals such as apatite, nepheline, alkaline pyroxenes and amphiboles, tantalo-niobates, rare earth carbonates, etc. isotope and geochemical data, in particular, the isotopic composition of carbon, oxygen, strontium. Problem statement. Most of the carbonate rocks that have certain characteristics of carbonatites cannot be attributed to this class, since they do not meet the selected criteria and do not contain traces of endogenous sources. An important problem is the choice of objective criteria for diagnosing endogenous carbonatitis and, on their basis, to outline promising areas for the search for new manifestations and deposits. Unresolved aspects of the problem. The genetic position of many manifestations of carbonate rocks remains uncertain. Such objects can be considered calciphyres, marbles, skarns and apatite-containing rocks of the Middle Pobuzhzhia (carbonate associations of the Zavalovskoye graphite deposit, magnetite calcifirs of the Moldovan iron ore deposit, carbonate veins with chromite of the Kapitanovskoye deposit, Troyaniv apatite manifestation) phlogopite calciphyrs of the Upper Pobuzhzhia (Lukashiv manifestation), as well as numerous metamorphic carbonate manifestations of the Priazovsky and Ingulets megablocks (Marble section of the Mangussky iron ore deposit). deposits, carbonate strata of the Kuksunguri iron ore deposit, calciphyra of the Starokrymska area on the periphery of alkaline massifs, Kazankovsky manifestation, etc.) The purpose of this article is to analyze the existing contradictory models of the genesis of carbonate-containing associations on the territory of Ukraine (mainly on the Ukrainian Shield) and to propose the most objective criteria for diagnosing true carbonatites. This will make it possible to conduct a more reasoned and effective search for these extremely important rocks from the point of view of the presence of strategic minerals in them. Presentation of the main material. In the first place among the reliably diagnosed carbonatites, in terms of size and variety of mineralization, is the Chernihiv alkaline-ultrabasic-carbonatite massif, the carbonate associations of which are typical representatives of this group of rocks. In addition, the Khlebodarovsky manifestation, veins and dikes meet certain criteria Oktyabrsky massif, Petrovo-Gnutivska dike, part of the carbonate rocks of the Malotersyansky massif. Conclusions. Promising areas of the Ukrainian shield for the search for carbonatites can be considered Pryazovsky, (continuation of the Khlibodarivska dike, Yuzhno-Kalchytskyi massif), Malotersyansky massif, and some manifestations of the Volyn megablock of the Shch (Berezova Gat structure). The Anadolskoye and Azov deposits of rare earths, where carbonate rocks have not yet been discovered, but there are geochemical and petrological prerequisites for the development of carbonatites (the existence of powerful zones of metasomatic processes of an alkaline nature, in particular phenitization, the presence of high concentrations of rare elements and accessory rare earth carbonates, etc.)